Civic participation as mediating variable between relationship of lifestyles, digital engagement and political participation among youths in Malaysia - Lai, Che Ching (2019)
The youth political participation has been on the declining trend in most democratic countries. However, studies have shown that youth political participation has strong link with their media usage. In addition, youth were known as being the heavy users of the digital media. Studies have also shown that civic participation among the youth was positively linked to political participation. The theoretical underpinning of the study was the Uses and Gratification theory (U&G) which suggested that gratification obtained, and media usage were two variables that were related. Thus, this study was conducted with the aims to examine the lifestyles, digital engagement, civic participation and political participation of youth in Malaysia. The study was also conducted to identify if civic participation mediates these relationships between lifestyles and political participation and digital engagement and civic participation. A quantitative survey method was conducted on 5237 respondents that were chosen through a stratified random sampling technique. These were youth aged between 15 to 25 years old. A set of questionnaires were used as the instrument for data collection. The lifestyles variable was measured through four domains namely; the media usage, religious and community services, recreation and vocational activities, and high-brow culture. The digital engagement measured the level of digital engagement. While the civic participation and political participation measured the activities that they were involved related to the variables. The data obtained for the study was analysed using descriptive analysis of frequency, percentage, mean and standard deviation. Linear regression analysis was used for the hypotheses testing while PROCESS mediation analysis was used to explain the mediation. The finding shows that the respondents were spending their leisure activities digitally engaged. Thus, suggesting a media-oriented lifestyle yet, they were only engaged at the basic level of the Internet usage, similarly with the digital engagement which was more on basic digital engagement as oppose to the advance digital engagement. The political participation of youth was low while the civic participation was slightly better. The relationships between the independent and dependent variables were positive, significant but at the moderate level. The civic participation of youth was found to mediate the relationships between the lifestyles of youth and digital engagement. Similarly, the civic participation also mediates the relationships between digital engagement and political participation. In terms of contribution to the body of knowledge, new approach for the U&G theory need to be considered in light with the interactivity feature offered by the media technology. The called for the theory to expand and include a broader outcome variable was supported. Newer measurement needs to be developed to capture the essence of youth consumption of the newer media in relations to their lifestyles as well as their civic and political participations. There were four major philosophical issues that warrant further investigation from the findings namely; the issues of preparedness of youth in embracing the advance level of digital engagement that will assist them for better political participation, the role of civic participation should be enhanced to induce better political participation; the lifestyles of youth is proven to be a predictor for youth political participation and finally, the implication of a serious generational gap between the youth and the older generation in the community.